2001
DOI: 10.1161/01.hyp.38.3.705
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Obesity Hypertension and Diabetes Syndrome

Abstract: Abstract-Obesity has been shown to be an independent risk factor for coronary heart disease. The insulin resistance associated with obesity contributes to the development of other cardiovascular risk factors, including dyslipidemia, hypertension, and type 2 diabetes. The coexistence of hypertension and diabetes increases the risk for macrovascular and microvascular complications, thus predisposing patients to cardiac death, congestive heart failure, coronary heart disease, cerebral and peripheral vascular dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
1
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 35 publications
0
70
1
3
Order By: Relevance
“…Because the occurrence of diabetes and hypertension are multiplicative risk factors for macro-and microvascular disease and determinants of cardiovascular outcomes, 42 the tight control of BP and glycemia in diabetic hypertensive patients is strongly recommended for preventing cardiovascular events. 43 In clinical practice, it is almost impossible to control the BP in diabetic patients without the use of diuretics.…”
Section: Magnesium and Hypertensionmentioning
confidence: 99%
“…Because the occurrence of diabetes and hypertension are multiplicative risk factors for macro-and microvascular disease and determinants of cardiovascular outcomes, 42 the tight control of BP and glycemia in diabetic hypertensive patients is strongly recommended for preventing cardiovascular events. 43 In clinical practice, it is almost impossible to control the BP in diabetic patients without the use of diuretics.…”
Section: Magnesium and Hypertensionmentioning
confidence: 99%
“…Antioxidant effects include inhibition of Ang II-and aldosteroneinduced superoxide formation [120,121], improvement in NO bioavailability [120,121], and reduction of oxidative stress [122,123]. CCBs have minimal effects on lipid levels [117,118,124,125].…”
Section: Mechanismsmentioning
confidence: 99%
“…ACE inhibitors may prevent or reduce Ang II-mediated interference with insulin-signaling pathways, evidenced by increased glucose transporter-4 protein content in skeletal muscle [147]. They may improve lipid levels by improving carbohydrate metabolism [125]. Their antioxidant effects include suppression of Ang II-induced superoxide formation [120,121] and reduction in oxidative stress [148,149].…”
Section: Mechanismsmentioning
confidence: 99%
“…Insulin resistance occurs in a wide variety of pathological states and is commonly associated with obesity, type 2 diabetes, accelerated atherosclerosis, and hypertension. 1,2 Shimamoto et al demonstrated that the insulin sensitivity of fructose-fed rats is improved by treatment with an Ang II receptor blocker (ARB), olmesartan, caused by changes in muscle fiber composition and a decrease in tumor necrosis factor (TNF)-␣ expression in skeletal muscle. 3,4 Henriksen et al 5 reported that an ARB, irbesartan, either acutely or chronically, improves glucose tolerance in the obese Zucker rat, at least in part through enhancement of skeletal muscle glucose transport, and the effect of chronic Ang II receptor antagonism on skeletal muscle glucose uptake is associated with an increase in GLUT4 protein expression.…”
mentioning
confidence: 99%